SOURCES AND DISTRIBUTION OF ORGANIC MATTER IN THE PLEISTOCENE-HOLOCENE SEDIMENTS OF NORTHERN BAIKAL (BY THE EXAMPLE OF N-ALKANE BIOMARKERS) - Afonina T.E.; Karabanov E.B. (My University, 2001)
We present new data on the distribution and composition of n-alkanes (biomarkers) and humic acids in the Holocene and Pleistocene bottom sediments of Northern Baikal accumulated under different sedimentation and paleoclimatic conditions. These data show significant amounts of allochthonous organic matter (OM) in the Holocene sediments of various sedimentation settings, which was supplied mainly with suspension flows. During glaciations, accumulation of both allochthonous and autochthonous OM was considerably reduced. In these periods, when no diatoms existed, autochthonous OM was produced from cyanobacteria and blue-green algae.
Keywords: Holocene; Pleistocene; Cenozoic::Quaternary::Holocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Голоцен; Кайнозой::Четвертичная::Плейстоцен